Konsep Bergaul bagi Perempuan dalam Al-Qur’an: Analisis Tafsir Quraish Shihab - Ningsih, Fitria (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2025)
Interaction is an extremely important aspect of human life, including for women. In Islam, the Qur'an provides guidance on social ethics that align with sharia values. However, the understanding of the concept of social interaction for women in the Holy Qur'an is still often misunderstood. Therefore, this study aims to discuss the concept of female social interaction based on an analysis of thematic interpretation (tafsir) to provide a comprehensive perspective. This research also has the objective to comprehensively understand the concept of women's social interaction in the Qur'an, identify relevant verses along with their interpretations (tafsir), and examine its implementation in daily life. Using Quraish Shihab's thematic tafsir method, this study examines verses such as QS. Al-Ahzab verse 32 and QS. An-Nur verse 31 as primary references. This study will explain how women's social interaction should be according to QS. An-Nur verse 31 and QS. Al-Ahzab verse 32 and its implementation in daily activities. This study is important to serve as a lesson on how to behave properly in accordance with the Qur'an.